Photocatalytic degradation of dye wastewater - Hamdan, Mohamad Alif Hakimi; Hairom, Nur Hanis Hayati; Ahmad, Mohd Khairul; Madon, Rais Hanizam; Abu Bakar Sidik, Dilaeleyana; Dzinun, Hazlini (Penerbit UTHM, 2020)
Dye wastewater is the major environmental issue of the textile and printing industries besides other minor issues like solid waste, health and safety. The use of synthetic chemical dyes in various manufacturing industrial process has increased considerably over the past decades, resulting in the release of dye-containing industrial effluents into aquatic ecosystem and soil [1]. Wastewater from printing and dyeing industries is frequently rich in color, containing residues of toxic chemicals, reactive dyes and requires proper treatment before all the effluent release into environment [2]. There are more than 8000 chemical products associated with all the dyeing, printing and finishing process listed in the color index, including some of the structural diverse of dyes, such as basic, acidic, reactive, disperse, azo, diazo, anthraquinone based and metal-complex dyes [1]. Therefore, these wastes must be genuine treated before it discharge to environment in order to comply with the environmental protection for the receiving water.